MECHANISM OF WATER DISTRIBUTION ON LEMON FARM LAND - Alfian Hamsi; Tulus Burhanuddin Sitorus (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Pump is mechanical device to increase the pressure energy of a fluid. Generaly pumps are used to lift the water from low level to high level. These are of two types,namely reciprocating pumps and centrifugal pumps. On centrifugal pumps the centrifugal force or variation of pressure due to rotation is responsible for their operation or working. The program of community services as implementation of sciences and technology intended to introduced and give skill training about water supply units to the community at Desa Sempa jaya ,Kabupaten Deli-Karo. In this area the people have a problem about availibity of water for agricultute, when mountain Sinabung gets eruption the leave of plantation are covered with dust and damaged to citrus plants,in dry season orange plants lack of water even though the success of the harvest is very dependent on water. The program was carried out by designing, fabricating and erecting the unit of water supply,consist of deepwell pump,piping system, valve,tee,bent,tower tank and panel control. The result of this community services showed that the capacity of pumps are 6 liter/menit,head are 50-70 meter,power 2 HP,speed 1500 rpm.capacity of tower tank 5400 liter, the pump may supply the water to tower tank until full about 2 hours,and the farmer may use the water from the tower tank by gravitation about 3 days.